곁가지 티올을 사용한 페로브스카이트 양자점의 리간드 교환 연구 - 유성민; Sung-min Yoo; 이명훈; Myong-hoon Lee; 하성민; Sung-min Ha; 장인수; In-su Jang; 이범주; Bumjoo Lee (한국화상학회지, 2021)
패로브스카이트 양자점의 리간드 교환을 통해 절대양자효율과 안정성이 향상되는 현상에 대해 연구를 수행하였다. 이를 위해 곁가지 구조를 가지는 리간드로서 2-ethylhexyl thioglycolate를 사용한 표면 부동태화를 통해 올레이트 리간드를 곁가지 티올 리간드로 교환하였다. 곁가지 구조의 티올 리간드는 패로브스카이트 양자점의 Br 결함을 채워 절대양자효율이 30%에서 80%로 급격히 향상되었다. 또한 용액상에서 안정성이 우수하고 필름 평가에서도 광학 특성이 향상됨을 확인하였다. FT-IR 분석을 통해 티올 리간드가 올레이트 리간드를 떼어내고 패로브스카이트 양자점 표면에 붙음을 확인하였고 XRD 분석을 통해 교환된 티올 리간드가 결정 구조를 변형시키지 않음을 확인하였다. We studied the ligand exchange effect of the perovskite quantum dot (PeQD) to improve the quantum efficiency and stability. Firstly, the oleate ligand of PeQD was exchanged with a branched thiol ligand, 2-ethylhexyl thioglycolate, by using a surface passivation method. It was believed that the branched thiol ligand filled the Br defect of PeQD, which dramatically improved the quantum efficiency from 30% to 80%. In addition, it was found that the dispersion stability in solution was excellent and the optical properties were improved in film as well. FT-IR analyses confirmed that the thiol ligand replaced the oleate ligand and firmly adhered to the PeQD surface, and the thiol ligand did not change the crystal structure, which was further confirmed through XRD analyses.